Predicting Cetacean Distributions in the Eastern North Atlantic to Support Marine Management - Correia, Ana M.; Sousa-Guedes, Diana; Gil, Ágatha; Valente, Raul; Rosso, Massimiliano; Sousa-Pinto, Isabel; Sillero, Neftalí; Pierce, Graham J. (Frontiers in Marine Science, 2021)
Data on species occurrence at the scale of their distributional range and the determination of their habitat use requirements are essential to support conservation and define management plans that account for their habitat requirements. For wide-ranging species, such as cetaceans, especially considering that their marine habitats include offshore areas, collection of such data is challenging. In the absence of dedicated surveys, alternative methodologies are needed, such as the use of data collected from platforms of opportunity and modelling techniques to predict distribution in unsurveyed areas. Using 6 years of cetacean occurrence data collected along cargo ship routes between the Iberian Peninsula, northwestern African coasts and the Macaronesian islands, we developed ecological niche models to assess habitat preferences and predict suitable habitats of the eight most frequently sighted cetacean taxa in the area. Explanatory variables used for model fitting included topographic, oceanographic, detectability, geographic and seasonal features. To provide a robust habitat characterisation, along with predictions of habitat suitability, making best use of occurrence datasets, we applied two modelling techniques, GAM and Maxent, which offer complementary strengths. Coastal areas provide important habitats for common and bottlenose dophins, while other dolphin species (spotted and striped dolphins) have a more oceanic distribution. The predicted niches of Cuvier’s beaked whale and minke whales are mainly in the high seas at northern latitudes. Suitable habitats for sperm whales and pilot whales are mostly in southern areas in continental slope regions. For all the species, models indicated that areas around seamount features offer suitable habitats, likely of high relevance in oligotrophic offshore waters. As such, dedicated survey effort in such areas would facilitate development and implementation of appropriate management plans, which are currently lacking. Our models offer an important contribution to baseline knowledge of cetacean distribution at basin-scale in the region and could support the definition of priority areas, monitoring plans, and conservation measures, essential to comply with the requirements of the EU Marine Strategy Framework Directive.